2022
DOI: 10.1186/s12913-022-08129-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of racism on First Nations patients' emergency care: results of a thematic analysis of healthcare provider interviews in Alberta, Canada

Abstract: Background First Nations people experience racism in society and in the healthcare system. This study aimed to document emergency care providers’ perspectives on care of First Nations patients. First Nations research partner organizations co-led all aspects of the research. Methods Sixteen semi-structured interviews were conducted with Alberta emergency department (ED) physicians and nurses between November 2019 and March 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“… 63 Indeed, in a previous publication, a physician participant noted how substance-using patients can be led to leave care by ignoring them. 60 This reflects a long-reported tendency for emergency departments to see patients who present with substance use as problems for their department’s operations, rather than presenting with medical issues pertinent to the emergency department. 64 Several of our qualitative examples of patients leaving related to mental health and substance use, while our quantitative data showed higher proportions of leaving without being seen or against medical advice among patients presenting for substance use and mental health problems (compared with injuries, infections, and women’s health issues) among both First Nations and non–First Nations patients, but with higher proportions among First Nations patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 63 Indeed, in a previous publication, a physician participant noted how substance-using patients can be led to leave care by ignoring them. 60 This reflects a long-reported tendency for emergency departments to see patients who present with substance use as problems for their department’s operations, rather than presenting with medical issues pertinent to the emergency department. 64 Several of our qualitative examples of patients leaving related to mental health and substance use, while our quantitative data showed higher proportions of leaving without being seen or against medical advice among patients presenting for substance use and mental health problems (compared with injuries, infections, and women’s health issues) among both First Nations and non–First Nations patients, but with higher proportions among First Nations patients.…”
Section: Discussionmentioning
confidence: 99%
“… 63 First Nations patients whose first language is not English may have language barriers, and communication issues can arise when providers and paperwork use unfamiliar, English-language medical terminology. In our previous study, some emergency providers in Alberta reported frustration with the communication style they perceived First Nations patients to use and made judgments about patients because of their First Nations “accent.” 60 Such factors put First Nations patients at a greater risk of poor communication and interactions with providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting gaps in health outcomes between Indigenous and non-Indigenous populations are a product of intertwined structures, power imbalances that reinforce social vulnerabilities, unfair distribution of economic and political goods and refusal to recognise or challenge the mechanisms and ideologies that target Indigenous peoples (Czyzewski, 2011). Moreover, research has evidenced that anti-Indigenous racism within Canadian healthcare systems is operationalised between and across multiple levels (Allan and Smylie, 2015;McLane et al, 2022;Roach et al, 2022Roach et al, , 2023Turpel-Lafond, 2021). Repeatedly, health service providers overlook, deny or disregard the distal determinants of health of Indigenous people as well as the structural barriers they endure (Czyzewski, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Different reports have shown that Indigenous communities have had traumatic experiences with the health care system, a system actively involved in colonial efforts, notably by enforcing medical experiments such as vaccine trials [ 23 , 24 ]. Decades later, recent reports also show that members of Indigenous communities continue to experience racism and discrimination within the health care system [ 25 , 26 ]. In addition to undermining trust, this has serious consequences on the health of these individuals, who often will not seek health services out of fear or shame [ 27 ].…”
Section: Introductionmentioning
confidence: 99%